Rodent management and cereal production in Asia: Balancing food security and conservation - Singleton, Grant R.; Lorica, Renee P.; Htwe, Nyo Me; Stuart, Alexander M. (Wiley, 2021)
Rodents present a major problem for food security in Asia where smallholder farming families are particularly vulnerable. We review here recent developments in the biology and management of rodent pests in cereal cropping systems in Asia. The past decade has seen a strong focus on ecologically‐based rodent management (EBRM), its adoption in field studies significantly increased rice yields (6–15%) and income (>15%) in seven Asian countries. EBRM principles have also been successfully applied to maize in China. We provide case studies on EBRM in Cambodia, on interactions between rodent pests and weeds, and on the importance of modified wetlands for biodiversity and rodent pest management. Knowledge on post‐harvest impacts of rodents is increasing. One research gap is the assessment of human health impacts from a reduction of rodent densities in and around houses. We identify 10 challenges for the next decade. For example, the need for population modelling, a valuable tool missing from our toolbox to manage rodent pests in cereal systems. We also need to understand better the interactive effects of cropping intensification, conservation agriculture and climate change. Finally, new management approaches such as fertility control are on the horizon and need to be considered in the context of smallholder cereal farming systems and mitigating health risks from zoonotic diseases associated with rodents. © 2021 The Authors. Pest Management Science published by John Wiley and Sons Ltd on behalf of Society of Chemical Industry.